2018
DOI: 10.1093/annonc/mdy444.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and comparison of CISNE model versus MASCC model in clinically stable febrile neutropenia patients

Abstract: Background: Patients with chronic or resolved hepatitis B virus (HBV) infection have a risk of reactivation after chemotherapy. Japanese guidelines recommend that all patients on chemotherapy should be screened for HBV infection. Although Asian peoples are considered to be a high risk population of HBV infection, little is known about the screening rate in Japan. Methods: We analyzed health insurance claims data linked with hospital-based cancer registry. Patients diagnosed with cancer in 2014, 20 years and ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…While ASCO includes both MASCC and CISNE cut-off 2 in its guidelines, we obtained the highest specificity (93.3%) and PPV (92.9%) by instead combining MASCC with CISNE cut-off 1. The performance characteristics that we report for both the CISNE score cut-offs and the MASCC score are similar to those previously reported in the literature in non-gynecologic populations ( Carmona-Bayonas et al, 2015 , Zheng et al, 2020 , Moon et al, 2018 , Ahn et al, 2018 , Koppaka et al, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…While ASCO includes both MASCC and CISNE cut-off 2 in its guidelines, we obtained the highest specificity (93.3%) and PPV (92.9%) by instead combining MASCC with CISNE cut-off 1. The performance characteristics that we report for both the CISNE score cut-offs and the MASCC score are similar to those previously reported in the literature in non-gynecologic populations ( Carmona-Bayonas et al, 2015 , Zheng et al, 2020 , Moon et al, 2018 , Ahn et al, 2018 , Koppaka et al, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…Two previous studies have analyzed the performance of CISNE scores in patients with solid malignancies. Research by Koppaka et al [11] also showed that CISNE scores had an AUROC of 0.846, whereas in Moon et al [7], CISNE scores had an AUROC of only 0.66. In our study, the population of solid malignancies was dominated by headneck malignancies, whereas previous studies showed head-neck malignancies in only 5% of populations.…”
Section: Discussionmentioning
confidence: 93%
“…67 (39,88) 26 (15,48) 20 (11,9) 24 (14,29) 11 (6,55) 20 (11,9) Chemotherapy The CISNE scores effectively predicted febrile neutropenia complications resulting from chemotherapy treatment of a solid malignancy with an AUROC of 0.893 (CI 95% 0.829-0.95; p = 0.03), whereas the MASCC scores with an AUROC of 0.77 (CI 95% 0.68-0.86; p = 0,04). Therefore, CISNE scores were found to be signi cantly better at predicting complications than MASCC scores in solid malignancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 There are also a limited number of studies comparing MASCC and CISNE scores, and there is no clear consensus on the usage of these scores. [11][12][13] In these studies, the superiority of the CISNE score to the MASCC score was not clearly demonstrated and thus the improvement of these scoring systems is needed for a more accurate risk stratification. 7,11 Albumin and globulin are the main proteins in serum.…”
Section: Introductionmentioning
confidence: 99%